Genetic Diversity of Botrytis cinerea Revealed by Multilocus Sequencing, and Identification of B. cinerea Populations Showing Genetic Isolation and Distinct Host Adaptation - Plesken, Cecilia; Pattar, Patrick; Reiss, Bianka; Noor, Zinnia Naoshin; Zhang, Lisha; Klug, Klaus; Huettel, Bruno; Hahn, Matthias (Frontiers in Plant Science, 2021)
Botrytis cinerea is a world-wide occurring plant pathogen, causing pre- and post-harvest gray mold rot on a large number of fruit, vegetable and flower crops. B. cinerea is closely related to B. pseudocinerea, another broad host range species which often occurs in sympatry with B. cinerea, and to several host-specific species including B. fabae and B. calthae. B. cinerea populations have been shown to be genetically heterogeneous, and attempts have been made to correlate genetic markers to virulence and host adaptation. Here, we present the development of a multilocus sequence typing (MLST) scheme, with ten genes selected for high variability and phylogenetic congruence, to evaluate the genetic diversity of B. cinerea, B. fabae and B. pseudocinerea. Using PacBio-assisted simultaneous mass sequencing of PCR products, MLST analysis of about hundred strains from diverse geographical origins and years of isolation was performed, which resulted in high resolution strain differentiation and robust species separation. Several B. cinerea strains formed an as yet unknown population, referred to as group B, which was well-separated from all other B. cinerea strains. Furthermore, the gene cluster for biosynthesis of the phytotoxin botcinic acid was missing in B. cinerea B strains. B. cinerea strains from the monocot Iris pseudacorus were found to form a genetically distinct population, and contained an intact gene cluster for production of the red pigment bikaverin, which is usually degenerated in B. cinerea. Remarkably, these strains were much more aggressive on Iris than other B. cinerea strains, which is the first unequivocal example for host specialization in B. cinerea. Our data reveal new insights into the genetic diversity of B. cinerea and provide evidence for intraspecific differentiation and different degrees of host adaptation of this polyphagous necrotrophic pathogen.